Comparative transcriptome analysis on the synthesis pathway of honey bee (Apis mellifera) mandibular gland secretions - YuQi Wu (Nature Portfolio, 2017)
Abstract Secretions from mandibular glands (MGs) have important caste-specific functions that are associated with the social evolution of honey bees. To gain insights into the molecular architecture underlying these caste differences, we compared the gene expression patterns of MGs from queens, queenright workers (WQRs) and queenless workers (WQLs) using high-throughput RNA-sequencing technology. In total, we identified 46 candidate genes associated with caste-specific biosynthesis of fatty acid pheromones in the MG, including members of cytochrome P450 (CYP450) family and genes involved in fatty acid β-oxidation and ω-oxidation. For further identification of the CYP450s genes involved in the biosynthesis of MG secretions, we analyzed by means of qPCR, the expression levels of six of the CYP450 genes most abundantly expressed in the transcriptome analysis across different castes, ages, tasks and tissues. Our analysis revealed that CYP6AS8 and CYP6AS11, the most abundantly expressed CYP450 genes in worker and queen MGs, respectively, are selectively expressed in the MGs of workers and queens compared to other tissues. These results suggest that these genes might be responsible for the critical bifurcated hydroxylation process in the biosynthesis pathway. Our study contributes to the description of the molecular basis for the biosynthesis of fatty acid-derived pheromones in the MGs.